Tanggung Gugat Ahli Waris Notaris terhadap Pewaris yang Dijatuhi Hukuman Ganti Rugi - Andi Fitra (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2017)
Authentic deeds in agreements made by notaries do not rule out the possibility to bring up legal matters and cause lawsuit case from the parties in the deed. The limitation of accountability of notaries can be required as long as they are still authorized to perform the duties of a notary. However, if the notary has passed away in the making of the deed, it becomes a legal matter and has harmed the parties. then what happens in interpretations of positive law is the one that must bear the punishment for damages made by the notary, based on a decision that has the legal binding verdict (inkracht) is the heir of the notary.